Moralee, J. (2018). Rome’s Holy Mountain. The Capitoline Hill in Late Antiquity - Millozzi, Sara (ARYS. Antigüedad: Religiones y Sociedades, 2020)
MORALEE, JASON (2018). Rome’s Holy Mountain. The Capitoline Hill in Late Antiquity. Oxford: Oxford University Press. 304 pp., 55,61€ [ISBN 978-0-1904-9227-4] [Book review]